Evaluating water productivity of tomato, pepper and Swiss chard under clay pot and furrow irrigation technologies in semi-arid areas of northern Ethiopia. (2018) - Gebru, Amanuel A.; Araya, Alemiea; Habtu, Solomon; Wolde-Georgis, Tsegay; Teka, Daniel; Martorano, Lucieta Guerreiro
Managing irrigation water is among the critical issues to address food insecurity under climate change and variability conditions. Irrigation is suggested as one of the adaptation practices commonly implemented to reduce climate related risks. However, there is scarcity of water in many drylands and identifying an efficient and effective irrigation system is crucial. A comparative study was undertaken between bar-shaped clay pot and furrow irrigation on tomato, pepper and Swiss chard crops in northern Ethiopia during the cropping season of 2014/2015. Results were compared on the basis of yield, water productivity and economic performance. The yields of Swiss chard, tomato and pepper were increased by up to 51, 32 and 30%, respectively, in bar-shaped clay pot irrigation system as compared to the control. Water saving was also considerably increased by 40.6, 41.2 and 41.7% for the respective crops as compared to the control. Similarly, the water productivities of Swiss chard, tomato and pepper were 10.9, 4.2, and 1.8 kg m –3, respectively. Further research on the suitability of bar-shaped clay pot irrigation on various soils and crops is recommended.